The impact of using digital books on the level of motivation of teachers and students to teach and learn mathematics in elementary schools in Palestinian Arab society in Israel - Yousef Methkal Abd Algani, Younis Fareed Abu Alhaija, Nayif Awad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study examines the impact of using digital books. Both on the effectiveness and efficiency of teachers' work in the teaching process and on students' motivation and involvement in the learning process in mathematics in elementary schools in Palestinian Arab society in Israel. Various studies have shown that using digital books to learn new content and ideas affects both the effectiveness and efficiency of teachers' work in the teaching process and the level of motivation of students and their involvement in the learning process. This issue has not been studied before among Palestinian Arab society in Israel, hence the uniqueness of this study. The case conducted using a quantitative methodology, in which 100 teachers and 270 students from elementary schools in Palestinian Arab society in the North of the country participated. The researchers used two questionnaires used to collect data pics related to the use of digital books in teaching and learning, the first of which was distributed among teachers and included four sections. The second questionnaire was distributed among the students and included six sections. The study's findings give an attitude towards using digital books and a positive contribution to the effectiveness and efficiency of the teachers' work in the teaching process. In addition, the study findings showed that the average level of motivation and involvement in the learning process among students who studied through digital books is higher than the average level of motivation and involvement in the learning process among students who did not study at all through digital books.